STUDY THE INDUMENTUM FOR SOME SPECIES OF EUPHORBIA L. (EUPHORBIACEAE) IN IRAQ - Zubaida A. Lattef Ismaeel,; Sukeyna Abaas Aliwy, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
This research was aimed to investigate 16 species belonging to the genus Euphorbia in order to enrich the Iraqi flora with diagnostic characteristics of this genus depending of the surface covering of leaves, stems and floral parts. The studied species were collected from Baghdad, Najaf, Karbala, Wasit, Diyala, Irbil, Kirkuk and Basrah in the growing seasons 2019/2020. These species are: Euphorbia. shehbaziana, E. denticulate Lam, E. craspedia Boiss., E., kete, E. pulcherrima, E. cyathophora Murray. E. granulata Forssk., E. helioscopia L., E. hirta L., E. hypericifolia L., E. milli Des Moul., E. puplus L., E. heterophylla L. , E. prostrata Aiton., E. microsphaera Boiss. and E. macrocarpa (Prokh.) Krylov. Results showed variations in types of trichomes which were glandular (stalked or sessile) or eglandular . The stalked glandular trichomes appeared only on the leaf and stem surfaces of E.craspedia and on the leaf surface of E.hirta. They were sessile glandular on the stem and floral surfaces of E.craspedia and leaf and floral part surfaces of E.cyathophora as well as floral parts of  both E.hypericifolia and E.milli.The plant parts of the same plant vary from glabrous to hairy. Some of the species do not have any type of trichomes in all the studied parts. These species were E. heterophylla , E. prostrata , E. microsphaera and E. macrocarpa.